The Characteristics of Islamic Ornaments on the Architecture of the Bujang Salim Mosque Krueng Geukeuh, Aceh - Nova Purnama Lisa; Armelia Dafrina; Deassy Sisca; Bambang Karsono (Faculty of Engineering, Malikussaleh University, 2018)
Ornamental architecture is a decorative art used to beautify parts of a building or object. Ornaments on the mosque are intended as decorative ornaments that can beautify the appearance of the mosque. Along with the development of the times and the influx of external culture, Islamic ornaments were also affected. Mosque architectural ornaments are influenced by external cultures in the form of mosque buildings and ornaments so as to create a new pattern, this pattern is what makes new patterns for decoration and beautifying mosques. The results of the characteristic analysis of Islamic ornaments in the Bujang Salim mosque are located, that the Islamic ornaments applied to the mosque buildings are influenced by the ornaments of local culture and outside culture, are the influence of Acehnese and Arabesque cultures. Islamic ornaments contained in the mosque have three characters, which are classified into floral motifs, geometry and calligraphy motifs, Islamic ornaments applied to the Great Mosque of Bujang Salim using basic embodiments and stylizations or compositions, namely the basic ornament forms adopted both locally and external cultures and change shape basic ornaments without removing the original form so that not much is modified. KEY WORDS: Ornament; Islamic architecture; Mosque